2001
DOI: 10.1177/00220345010800020201
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship among Dental Status, Nutrient Intake, and Nutritional Status in Older People

Abstract: Dental health status may influence nutrition. The objective of this part of the National Diet and Nutrition Survey was to assess if there is a relationship between dental status in people 65 years and older and intake of certain nutrients and any link between dental status and blood-derived values of key nutrients. Random national samples of independently living subjects and those living in institutions had dental examinations, interviews, four-day food diaries, and blood and urine analyzed. In the sample livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
443
5
41

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 500 publications
(512 citation statements)
references
References 23 publications
23
443
5
41
Order By: Relevance
“…Vol 44 No 6 and 178 women remained to be studied. Number of teeth was still found to be significantly inversely associated with heart rate (P = 0.034).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vol 44 No 6 and 178 women remained to be studied. Number of teeth was still found to be significantly inversely associated with heart rate (P = 0.034).…”
Section: Resultsmentioning
confidence: 99%
“…Data collection: The examination included completion of a medical questionnaire including questions regarding smoking history, physical activity, and alcohol consumption. All subjects except those who lived in two cities (Buzen City Vol 44 No 6 and Yukuhashi City; 130 subjects) were questioned as to any medications they were currently taking. Serum total cholesterol and creatinine concentrations were measured.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this study have important implications for public health policy. Previous analyses of these data have shown that people with fewer than 20 teeth had dietary restrictions 3 and nutritional deficiency 5 when compared with those with 20 or more teeth. The findings reported here provide further scientific evidence for 20 or more natural teeth being a reasonable threshold for acceptable oral health and a functional dentition into old age.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Tooth loss has been associated with changes in diet preference and nutritional deficiency. 5,6 In previous reports, [7][8][9] researchers demonstrated that 80-yearolds who were physically active retained a higher number of their teeth and had a higher bone density than 80-year-olds who were not active. Tooth loss appears to be a predictor of abnormal electrocardiography findings, including ST depression, T-wave abnormalities, and arrhythmias.…”
Section: Introductionmentioning
confidence: 99%